1989
DOI: 10.1557/proc-178-159
|View full text |Cite
|
Sign up to set email alerts
|

Class F Fine Fly Ash

Abstract: The Taiwan Power Company's (TPC) coal combustion power plants produced approximately 1 million tons of class F fly ash in 1988 but only 25% of it was effectively utilized. Accordingly, this study investigated the use of separation techniques to improve the quality of the fly ash in order to increase its application. In the experiment, the fly ash was dry-sieved through sieves No. 200, 300 and 400 mesh respectively. The chemical, physical and some of the engineering properties of those classified class F fine f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1997
1997
2012
2012

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…200 sieve (0.075 mm). Sheu et al (1990) reported that most fly ash investigated passed the No. 400 sieve (0.0325 mm) with only 6% of fly ash being retained on the No.…”
Section: Grain Size Distributionmentioning
confidence: 99%
“…200 sieve (0.075 mm). Sheu et al (1990) reported that most fly ash investigated passed the No. 400 sieve (0.0325 mm) with only 6% of fly ash being retained on the No.…”
Section: Grain Size Distributionmentioning
confidence: 99%
“…Some particles may be rounded or rodshaped (Huang 1990). Slags from lignite and sub-bituminous coals tend to be more vesicular than slags of the eastern bituminous coal (Huang 1990 (Sheu et al 1990) the crushing process, the particle shapes become more angular. (Huang 1990 (Huang 1990 (Ke 1990 (Huang 1990 Nevertheless, due to the complex pore structure of bottom ash aggregates, irregular response to compaction may be produced (Huang 1990 (Huang 1990 (Huang 1990 (Huang 1990).…”
mentioning
confidence: 99%